Penerapan Good Handling Practices (GHP) dan Optimalisasi Solar Dryer Tipe Rak untuk Meningkatkan Mutu Biji Kopi Kelompok Tani Karya Makmur Sidomulyo, Kecamatan Air Naningan, Kabupaten Tanggamus - Novita, Dwi Dian; Suharyatun, Siti; Amien, Elhamida Rezkia; Asropi, Asropi (Research and Social Study Institute (RESSI), 2024)
Coffee is one of the strategic plantation commodities that significantly contributes to the economy in Indonesia. The lack of proper post-harvest handling of coffee has resulted in the low quality of coffee beans produced by farmers affiliated with the Karya Makmur Farmer Group. This activity aims to (1) provide technical guidance on proper post-harvest handling of coffee to partner farmers, (2) modify drying racks and air circulation systems to enhance the capacity of the solar dryer dome, and (3) improve the quality of coffee beans produced in accordance with general coffee quality standards. The implementation of the activity has been successful, yielding the following results: 1) There has been an increase in knowledge and skills among members of the Karya Makmur farmer group in post-harvest coffee handling according to Good Handling Practices (GHP), 2) The Outreach Team has constructed one unit of a stacked-rack solar dryer with a drying capacity of 450 kg as an additional drying tool that can be utilized by the group, 3) The performance of the stacked-rack solar dryer produces better quality coffee beans compared to drying using the solar dryer stackted rak or sun-drying on the ground, and 4) The use of the stacked-rack solar dryer is effectively utilized by the Karya Makmur farmer group in the drying process of fresh coffee beans as well as for other commodities.